A reversible steganographic scheme for VQ indices based on joint neighboring coding. Issue 2 (1st February 2015) - Kieu, The Duc; Ramroach, Sterling
Highlights A novel reversible steganographic scheme for VQ indices based in joint neighboring coding is proposed. The proposed scheme can embed n secret bits into one VQ index, where n = 1, 2, 3, or 4. The proposed scheme can provide high embedding rates, low bit rates, and high embedding efficiencies.